Pijat Bayi terhadap Kualitas Tidur pada Bayi Usia 1-12 Bulan - Erlina Erlina; Fatiyani Fatiyani; Nizan Mauyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of infant massage on the sleep quality of infants aged 1-12 months in Langa Village, Syamtalira Bayu District, North Aceh District. The research method was pre-experimental with a one-group pretest-posttest design. The study found that 92% of mothers did not massage their babies, with the pre-test results for the quality of their baby's sleep in the